New records of fishes from Guadalupe Island, northwest Mexico - Walther-Mendoza, Mariana; Ayala-Bocos, Arturo; Hoyos-Padilla, Mauricio; Reyes-Bonilla, Héctor (HIDROBIOLÓGICA, 2017)
The icthyofauna from Guadalupe Island, Mexico, has been scarcely studied. This paper presents additions to the systematic checklist of fishes from that oceanic island, and is based on data obtained from museums, field records and international databases. A total of 22 new records are depicted for the locality (19 deep-water species and 3 shallow reef-dwelling fishes), including one addition to the Mexican fauna (Nansenia candida). These reports complement the previous list of 328 species for Guadalupe Island,which now reaches 350 species, distributed in 5 classes, 44 orders and 127 families.